Urban planning as a territorial transformation policy: The case of Lincoln Plaza mall territorialization, Moravia, Costa Rica - Jiménez Corrales, Andrés (2020)
Urban planning is often interpreted as a technical-objective instrument. This fact hides the real political interests that drive the formulation, concretion and modification of territorial planning instruments. Through the case study of Lincoln Plaza mall territorialization, the article sets out arguments to discuss the premise presented. To do this, it uses as a methodology the review of documents, such as municipal records, journalistic news, bibliography and interviews. Results demonstrate the creation of public-private support for Lincoln Plaza mall building, achieved through a transformation of the local territorial planning instrument and influenced by particular and private interests.